Using the Canva Application in Writing News Texts at Hadziqiyyah Integrated Vocational School, Jepara - Herwani, Suci (Proceeding International Conference on Religion, Science and Education, 2024)
This research aims to describe the use of the Canva application in writing news texts and analyze errors in using various languages in writing news texts at Hadziqiyyah Jepara Integrated Vocational School. This type of research is descriptive with qualitative research methods. The research data consists of student responses in writing news texts using the Canva application as well as quotes from news texts written by Hadziqiyyah Integrated Vocational School students. The data collection method uses a questionnaire sheet to describe students' responses to using the Canva application in writing news texts, as well as giving a news text writing test to analyze errors in using various languages in writing news texts. Data collection techniques use listening and note-taking techniques. The data presentation method uses informal methods, while the data analysis method uses contextual analysis methods. The research results showed that students' responses were very enthusiastic about using the Canva application in writing news texts, while errors in using various languages in writing news texts included inaccurate sentence structures and inaccurate writing of Enhanced Spelling (EYD). Inaccuracy in sentence structure occurs when the choice of words (diction) is incorrect, resulting in the sentence being written to be ineffective. Apart from diction, the cause of inaccurate sentence structure occurs due to word scattering. Inaccuracies in writing EYD are found in capital letters, abbreviations, prepositions in, affixations in-, and standard words.